Genome scale analysis of cellular processes using RNAi - Kiger, Amy (Henry Stewart Talks, 2008)
Functional analysis in Drosophila, RNAi, Genetic screens by RNAi, RNAi libraries, Cell-based assays, Screen analysis, Systematic analysis of high-throughput data, Normalization and hit identification, Challenges in quantitative image analysis, Issues and insights from screen results, Applications for RNAi screens, Assay for cell fitness, Assay for cell morphology, Shared defects and shared pathways, Outlook for RNAi screens
Reviewed at 2018/05/31